Numerical modelling of stiffness of RTA furniture with new externally invisible and dismountable joints : Numeričko modeliranje krutosti RTA namještaja s novim, izvana nevidljivim vezovima - Krzyżaniak, Łukasz (Array, 2020)
The distribution of furniture sold in the form of flat packages requires the use of appropriate design solutions. These include joints, which need to facilitate self-assembly with no need to use tools. Such joints should be functional, aesthetically attractive, durable and safe to use. It was decided in this study to manufacture prototypes of innovative furniture joints and evaluate the quality of furniture assembled using these joints. For this purpose, the finite element method and the Abaqus program were used. Joints were modelled as objects made of polylactide (PLA). Surface to surface contact and assembly forces resulting from the construction of joints were introduced between the elements of the joint. The furniture case was subjected to torsional loads. The rigidity of furniture and stress distribution in joints were calculated. On the basis of numerical calculations, the joints were positively validated.